The teaching in non-formal education: learning from a teacher in training - Baptistella, Bruna Fabiane; Chaluh, Laura Noemi (Revista Hipótese, 2015)
n this article we share the experience of a training teacher who started in the teaching profession in the context of a social project developed by an NGO in a city in the state of São Paulo. The social project helps six- to fourteen-years-old children that are at social risk in the turn they are not in school, and aims to guide children and adolescents developing activities in education, health, social orientation and sports. In this work, we problematize the concept of formal and non-formal education in an attempt to understand which experiential knowledge was learned by the training teacher when in touch with a work approach that differed from proposals developed in the school context.
Keywords: Non-formal education; Pedagogical practice; Teaching